The impact of rural tourism entrepreneurs' hometown identity on entrepreneurial persistence - Fuhua Xiang (Frontiers in Psychology)
IntroductionThis study explores how hometown identity of rural tourism entrepreneurs affected entrepreneurial persistence.MethodsData from 494 rural tourism entrepreneurs were collected using convenience sampling and analyzed using Amos and SPSS statistical software package via questionnaires distributed to three villages in Guizhou province, China.ResultThe findings reveal that (1) rural tourism entrepreneurs' hometown identity positively affected their attitudes toward entrepreneurial persistence and indirectly influenced entrepreneurial persistence; (2) rural tourism entrepreneurs' hometown identity positively influenced perceived behavioral control and indirectly affected entrepreneurial persistence; (3) rural tourism entrepreneurs' hometown identity positively moderated the role of subjective norms on entrepreneurial persistence.DiscussionThe findings from the present study indicated that rural tourism entrepreneurs' hometown identity can shape entrepreneurial persistence through numerous means. Authorities should emphasize the cultivation of a strong hometown identity among entrepreneurs when formulating and implementing destination-related policies to ensure the sustainable development of rural tourism.